Multiple Tolerization Subtractive Immunization in the Obtention of Specific Monoclonal Antibodies Against Paracoccidioides lutzii - Neves, Franciny Mara de Lima [UNESP]; dos Santos, Kelvin Sousa [UNESP]; dos Santos, Rafaela Cristine [UNESP]; de Lima Fontes, Marina; Marcos, Caroline Maria [UNESP]; do Araujo, Vileneide Santana [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Moroz, Andrei [UNESP] (SAGE Publications, 2024)
Paracoccidioidomycosis (PCM) is a chronic endemic mycosis in Latin America, predominantly caused by Paracoccidioides brasiliensis (Pb18) and Paracoccidioides lutzii (Pl01). Diagnosing PCM is challenging due to species-specific antigenic differences, therefore new biomarkers for accurate and rapid detection are needed. This study explores multiple tolerization subtractive immunization (MTSI) to generate monoclonal antibodies against rare or weakly expressed epitopes of Pb18 and Pl01, potentially improving PCM diagnosis. These strains were cultured to obtain cell-free antigens (CFA). MTSI involved immunizing BALB/c mice with CFA from Pb18 as a tolerogen and Pl01 as an immunogen, using Freund’s adjuvant and cyclophosphamide to induce immune tolerance. The immune response was monitored via Enzyme-linked immunosorbent assay (ELISA) and Western blotting. Hybridomas were generated by fusing splenocytes from immunized mice with myeloma cells, after which clonal selection was conducted based on reactivity to Pl01 antigens. The study explores the presence of various proteins, including gp43 and Hsp60, in the protein profile of CFAs. Additionally, polyclonal antibody reactivity to Pb18 antigens was significantly reduced, suggesting that MTSI effectively promoted immunological tolerance. Followig the screening of hybridomas, clones with good reactivity to Pl01 and less reactive to Pb18 were selected. The monoclonal clones C1 and E6 exhibited potential specificity for Pl01 antigens. The effective generation of P. lutzii-specific antibodies by MTSI demonstrates this technology’s promise for the development of accurate PCM diagnostic instruments. These antibodies have the potential to enhance patient outcomes and reduce the incidence of false-negative diagnoses, which could lead to better disease management.
Keywords: biomarkers; diagnosis; monoclonal antibodies; multiple tolerization subtractive immunization; Paracoccidioides brasiliensis; Paracoccidioides lutzii